A Bibliometric Analysis of Research Trends in Parental Management and Learning Achievement: Global Perspectives and Future Directions - Muslimin, Afif Ikhwanul (Journal of Data Science, Informetrics, and Citation Studies)
The objective of this study is to conduct a bibliometric analysis of research trends in parental management and learning achievement, aiming to map the evolution of scholarly focus in this area and identify emerging themes. Utilizing the Scopus database, the research examines publication patterns, authorship, and keyword co-occurrence to provide a comprehensive overview of the landscape of parental involvement in education. The findings reveal a significant increase in publications over the past decade, peaking in 2021, which indicates a growing interest in understanding the multifaceted ways parents influence their children's academic outcomes. The analysis highlights the prominence of international collaborations, suggesting a broader, cross-cultural examination of parental involvement. Additionally, emerging areas of interest, such as the role of technology in education and the psychological factors associated with parental management, are identified. The implications of this research underscore the global relevance of parental management in education and the necessity for future studies to address gaps in the literature, particularly in underrepresented regions. By expanding data sources and incorporating qualitative methods, researchers can gain deeper insights into the contextual nuances of parental involvement, ultimately informing educational practices and policies that enhance student learning outcomes across diverse settings.
Keywords: Bibliometric analysis; Learning achievement; Parental management; Research trends.